If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5secx + -6 = 5 Reorder the terms: -6 + 5cesx = 5 Solving -6 + 5cesx = 5 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 5cesx = 5 + 6 Combine like terms: -6 + 6 = 0 0 + 5cesx = 5 + 6 5cesx = 5 + 6 Combine like terms: 5 + 6 = 11 5cesx = 11 Divide each side by '5esx'. c = 2.2e-1s-1x-1 Simplifying c = 2.2e-1s-1x-1
| 6x^2+10x=-2 | | 11(t-5)+4t=5(3t+3)-8 | | 13+2x=3x | | -4x+13=-2x-11 | | -3(11b+7)=-12(2b-8) | | (y-8)-(y+9)=6y | | 11x-2=119 | | 3x^2-x=102 | | -12=7-5-6n+11 | | (x+8)-14=2 | | 0=x^4-625 | | v=2x(18-2x)(24-2x) | | 2+8n=4(1+2n) | | 4(2x+6)=5(x+4)+x | | 1600=16x^2 | | 12.56=3.14(5)(15.7)h | | 4x+14=2-2x | | -7x^2-4x-7+x^2-5x^2+x^3+8x-2x^3= | | 12+5t=6(1t+2) | | 4ln(x+3)-9ln(x)=0 | | 0.04(2x+7)=0.08(t-5)+0.68 | | -7x^2-4x-7+x^2-5x^2+x^3+8x+5= | | 2y+8-2y=4y | | -(1-2n)=17+8n | | 12.56=3.14(5)(2)h | | -37+x=-2+11 | | 4(11-9)-7(6a)= | | -5x^4-x^2+8x^3+4x+2x^4-x^3+x^2= | | 4x^2+18-3x=0 | | x-(-5)=30 | | 4x-5x+6x=-90 | | 5x+3(1+x)=-21+2x |